The Training Function of Evaluation in Everyday School Work - Segura Castillo, Mario Alberto (2017)
The formative function, which purpose is to regulate the educational process in the classroom, meaning the daily school work, which is integrated to the didactic intervention since it is focused on the processes rather than on the learning outcomes, for what the feedback-that is obtained is of qualitative character, allows to detect the learning barriers for the development of the pedagogical mediation of the student body. The aim of this research is to reflect on the opinion of the teachers of the III Cycle and Diversified Education of the Costa Rican Educational System, with the purpose of enriching the evaluation practice with aspects that have not been important to this day such is the case of the formative function that entails taking into account diversity from processes such as feedback, feedback, sustainability of assessment and barriers to learning. It is concluded that the teaching staff observed and subsequently interviewed still cannot be clear how the daily work component is qualified.